Quantifying Sustainability Trade-offs in Forest Licensing (IPPKH): A Multi-Criteria Analysis of Ecological, Social, and Economic Outcomes - Soedarto, Teguh; Sahbuddin (Tarjih : Agribusiness Development Journal, 2025)
Indonesia’s Forest Area Borrow-Use Permits (IPPKH) aim to balance economic development with environmental and social safeguards, yet their implementation has often exacerbated sustainability trade-offs, including ecological degradation, social conflict, and inequitable benefit-sharing. This study addresses critical governance gaps—such as weak participatory mechanisms, opaque monitoring, and centralized decision-making—by proposing an innovative, multi-stakeholder model for IPPKH management. Combining mixed-methods research, including multi-criteria decision analysis (MCDA), geospatial assessments, and participatory stakeholder evaluations, the study evaluates three high-conflict IPPKH sites in Kalimantan, Papua, and Sumatra. The proposed model integrates four pillars: (1) sustainability principles (ecological, social, and economic balance), (2) participatory governance (Free, Prior, and Informed Consent—FPIC, and multi-stakeholder forums), (3) community-based monitoring, and (4) equitable benefit-sharing mechanisms. Empirical results from pilot implementations showed a 62% reduction in conflicts, a 15% improvement in vegetation cover (NDVI), and a 12% rise in local household incomes. The study’s key innovation lies in its dynamic, cyclical framework, which uses quantifiable indicators to assess trade-offs and guide adaptive management. Policy recommendations include reforming Government Regulation No. 23/2021 to institutionalize participatory processes and introducing fiscal incentives for ESG-compliant companies. The model’s scalability across sectors like mining and plantations offers broader applications for sustainable resource governance. Limitations include the need for longitudinal studies and testing in politically complex regions like Papua. By bridging policy gaps with actionable tools, this research advances Indonesia’s commitments to climate resilience, environmental justice, and inclusive development under the SDGs and Paris Agreement.